2007
DOI: 10.1097/mbc.0b013e3280111a8e
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastographic measures of clot propagation: a comparison of alpha with the maximum rate of thrombus generation

Abstract: The alpha angle alpha (degrees) is a thrombelastographic measure of clot propagation. A parametric measurement of clot propagation [maximum rate of thrombus generation (MRTG), dynes/cm2 per s], however, has recently been utilized. Thus, the relationship of changes in alpha with changes in MRTG were determined. alpha and MRTG values obtained from 859 thrombelastograms was collected from nine studies. Data were analyzed and the relationship between alpha and MRTG defined with commercially available software. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 11 publications
2
33
0
Order By: Relevance
“…We found two additional studies using the same methodology we used and reporting on reference normal values. Ellis et al (33), investigating clot propagation, reported on 33 normal individuals ranging in age from 18 to 65 years and using both plasma and whole blood. Another study by Chan et al (34) reported normal values in a pediatric population of 100 children undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…We found two additional studies using the same methodology we used and reporting on reference normal values. Ellis et al (33), investigating clot propagation, reported on 33 normal individuals ranging in age from 18 to 65 years and using both plasma and whole blood. Another study by Chan et al (34) reported normal values in a pediatric population of 100 children undergoing surgery.…”
Section: Discussionmentioning
confidence: 99%
“…and maximum clot firmness with new dynamic parameters such as maximum velocity of clot formation and the time to maximum velocity of clot formation [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to conventional TEG parameters, it also has the advantage of measuring the functionally relevant 133,134 clot resistance directly. 135 We also note a number of approaches to the development of coagulometry based on the measurement of the passive electrical properties of the sample, [136][137][138][139][140][141][142] a strategy that we ourselves have found useful, 143 with radio-frequency measurements of cellular properties having a particular value. [144][145][146][147] Finally, fibrin scatters light much more than does fibrinogen such that turbidimetry is often used to detect its formation (e.g.…”
Section: The Clot Lifespan Modelmentioning
confidence: 99%